Green performance enhancement of marine engines via turbocharger compression ratio optimization - Saad S. Alrwashdeh; Mohammad R. Almajali; Falah Mustafa Alsaraireh; Ala’ M. Al-Falahat (Results in Engineering)
This study investigates the performance dynamics of a six-cylinder, inline compression ignition engine, focusing on its response to varying turbocharger compressor pressure ratios (TCPRs). At a constant speed of 1500 RPM, the engine's power output, braking mean effective pressure, and brake torque increase significantly, ranging from 280 kW, 11.7 bar, and 1779.7 N m at a TCPR of 2–1042.6 kW, 43.7 bar, and 6637.8 N m at a TCPR of 10. This demonstrates a direct relationship between TCPR and engine performance metrics. Additionally, mechanical efficiency improves with increasing TCPR, indicating enhanced adaptability and efficiency of the engine. The study analyzes the effects of turbochargers, exhaust and intake characteristics, NOx emissions, combustion dynamics, and compressor settings, providing a comprehensive understanding of the relationship between turbocharging and compression ignition engines. These insights can support future research aimed at optimizing engine performance across various TCPR settings.